Sustainable river water quality management in Malaysia - Al-Mamun, Abdullah; Zainudin, Zaki (IIUM Press, 2013)
Ecological status of Malaysia is not as bad as many other developing nations in the world. However, despite the enforcement of the Environmental Quality Act (EQA) in 1974, the water quality of Malaysian inland water (especially rivers) is following deteriorating trend. The rivers are mainly polluted due to the point and nonpoint pollution sources. Point sources are monitored and controlled by the Department of Environment (DOE), whereas a significant amount of pollutants is contributed by untreated sullage and storm runoff. Nevertheless, it is not too late to take some bold steps for the effective control of non-point source pollution and untreated sullage discharge, which play significant roles on the status of the rivers. This paper reviews the existing procedures and guidelines related to protection of the river water quality in Malaysia. There is a good possibility that the sewage and effluent discharge limits in the Environmental Quality Act (EQA) may pose hindrance against achieving good quality water in the rivers as required by the National Water Quality Standards (NWQS). For instance, Ammoniacal Nitrogen (NH3-N) is identified as one of the main pollutants to render many of the rivers polluted but it was not considered in the EQA as a monitoring parameter until the new regulations published in 2009. Surprisingly, the new regulation for sewage and industrial effluent limits set allowable NH3-N concentration quite high (5 mg/L), which may result in low Water Quality Index (WQI) values for the river water. The water environment is a dynamic system. Periodical review of the monitoring requirements, detecting emerging pollutants in sewage, effluent and runoff, and proper revision of water quality standards are necessary for the management of sustainable water resources in the country.